Erector spinae plane block with catheter infusion for analgesia in a patient undergoing transaxillary first rib resection. Issue 2 (19th October 2022) - McCance, L.; Smith, E. C.; Moore, J.; Forget, P.
Summary: Analgesia for first rib resection can be challenging with short‐ and long‐term consequences for patients such as acute distress, difficulty participating in physiotherapy and chronic pain. We report utilising an erector spinae plane block with a continuous infusion catheter as analgesia for a transaxillary first rib removal in a patient with venous thoracic outlet syndrome (Paget‐Schroetter syndrome). We could find no reports of erector spinae plane block in transaxillary rib resection, and a limited number of reports using a paravertebral approach to analgesia for this procedure. In our case, an erector spinae plane block provided effective analgesia, allowing the patient to participate freely in postoperative physiotherapy; no complications of erector spinae plane block were encountered. Further research into the safety and efficacy of erector spinae plane block for first rib resection is warranted.